СИСТЕМИ ФАЗОВОГО АВТОПІДЛАШТУВАННЯ ЧАСТОТИ РЕЗОНАНСНИХ ІНВЕРТОРІВ УСТАНОВОК ІНДУКЦІЙНОГО НАГРІВАННЯ ЗА НИЗЬКОЇ ДОБРОТНОСТІ КОЛИВАЛЬНОГО КОНТУРУ - Гуцалюк, В.Я.; Зубков, І.С. (Інститут електродинаміки Національної академії наук України, 2019)
Phase-locked loop (PLL) systems in control circuits of resonant voltage inverters of high-frequency induction heating installations are used for getting the maximal active power in the load and minimal power losses in converter transistors under a wide range of load settings. In the paper, it is shown study results of the Q-factor influence of the voltage inverter’s load series resonant circuit of the induction heating installations on the accuracy of the PLL system. Under low values of the Q-factor, which is, for instance, equal 2, switching current may increase up to 30 % in comparison to that under high Q-factors; this, respectively, increases power losses under transistors switching. To provide optimal modes of their switching it is necessary to lower the transistor control pulse delay time depending on the Q-factor of the inverter load circuit. References 8, figures 7.